2007
DOI: 10.1890/06-1620.1
|View full text |Cite
|
Sign up to set email alerts
|

Endemic Hantavirus Infection Impairs the Winter Survival of Its Rodent Host

Abstract: The influence of pathogens on host fitness is one of the key questions in infection ecology. Hantaviruses have coevolved with their hosts and are generally thought to have little or no effect on host survival or reproduction. We examined the effect of Puumala virus (PUUV) infection on the winter survival of bank voles (Myodes glareolus), the host of this virus. The data were collected by monitoring 22 islands over three consecutive winters (a total of 55 island populations) in an endemic area of central Finlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 37 publications
4
104
2
Order By: Relevance
“…While this still occurs, it is now accepted that evolution towards intermediate, or in rare cases, severe host damage can enhance parasite fitness (Ewald 1994, Nunn andAltizer 2006). In support, a growing body of research has revealed subtle effects of endemic parasites on both the reproduction and survival of wildlife species (Hudson et al 1998, Tompkins and Begon 1999, Bize et al 2004, Hakkarainen et al 2007, Kallio et al 2007. Nevertheless, experimental evidence of parasite effects on wildlife populations remains rare and valuable (Begon et al 2006).…”
Section: Effects Of Parasites On Host Populationsmentioning
confidence: 99%
“…While this still occurs, it is now accepted that evolution towards intermediate, or in rare cases, severe host damage can enhance parasite fitness (Ewald 1994, Nunn andAltizer 2006). In support, a growing body of research has revealed subtle effects of endemic parasites on both the reproduction and survival of wildlife species (Hudson et al 1998, Tompkins and Begon 1999, Bize et al 2004, Hakkarainen et al 2007, Kallio et al 2007. Nevertheless, experimental evidence of parasite effects on wildlife populations remains rare and valuable (Begon et al 2006).…”
Section: Effects Of Parasites On Host Populationsmentioning
confidence: 99%
“…In the most extreme cases, epizootic outbreaks may cause large-scale, stochastic population die-offs [1,2]. A small but growing body of research has identified more subtle effects of pathogens on host reproduction and survival [3][4][5][6]. However, experimental evidence for pathogen-induced population limitation in natural settings is rare (but see [3,7]).…”
Section: Introductionmentioning
confidence: 99%
“…However, some recent studies no longer support this view. Besides negative effects at the cellular level (Netski et al, 1999) and on body weight (Douglass et al, 2007), indications of lowered host survival due to hantavirus infection have been reported (Douglass et al, 2001;Calisher et al, 2005;Kallio et al, 2007). Furthermore, because of the chronic infection that hantaviruses induce in their host, they are likely to impose a high resource cost throughout their host's lifetime by triggering specific immune responses (Lehmer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%